Police [compact disc, unabridged] - Nesbø, Jo, 1960- (Nesbø, Jo, 1960- Harry Hole series., 2013)
The police urgently need Harry Hole ... a killer is stalking Oslo's streets. Police officers are being slain at the scenes of crimes they once investigated but failed to solve. The murders are brutal, the media reaction hysterical